2020
DOI: 10.1111/pcmr.12925
|View full text |Cite
|
Sign up to set email alerts
|

NRASQ61K melanoma tumor formation is reduced by p38‐MAPK14 activation in zebrafish models and NRAS‐mutated human melanoma cells

Abstract: Oncogenic BRAF and NRAS mutations drive human melanoma initiation. We used transgenic zebrafish to model NRAS‐mutant melanoma, and the rapid tumor onset allowed us to study candidate tumor suppressors. We identified P38α‐MAPK14 as a potential tumor suppressor in The Cancer Genome Atlas melanoma cohort of NRAS‐mutant melanomas, and overexpression significantly increased the time to tumor onset in transgenic zebrafish with NRAS‐driven melanoma. Pharmacological activation of P38α‐MAPK14 using anisomycin reduced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…Hep3B and HCCLM3, two cell lines with weak phosphorylation of p38 MAPK, were chosen for subsequent experiments of activation of p38 MAPK. Anisomycin treatment was applied to the two cell lines to investigate the anticancer effects of p38 MAPK activation on HCC cells [14][15][16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hep3B and HCCLM3, two cell lines with weak phosphorylation of p38 MAPK, were chosen for subsequent experiments of activation of p38 MAPK. Anisomycin treatment was applied to the two cell lines to investigate the anticancer effects of p38 MAPK activation on HCC cells [14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…More interestingly, noncoding RNAs have also been reported to be involved in the axis of p38-ferroptosis [11,12]. Moreover, an agonist of p38 MAPK, anisomycin [13], has also shown its potential value in medication, as it could significantly induce cell death in acute lymphoblastic leukemia, melanoma, and glioma [14][15][16][17][18]. Kim et al [19] described that anisomycin could exert both direct killing effects and immunotherapeutic effects mediated by natural killer cells (NK) in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, targeting of the CoREST complex with the small-molecule inhibitor corin led to increased expression of p38i dosing (Supplemental Figure 9, G and H and Supplemental Tables 11 and 12). Recent studies in a zebrafish melanoma model (39) suggest that p38 MAPK functions as a tumor suppressor in NRAS-mutant melanomas. We therefore explored the role of DUSP1/p38 MAPK in NRAS-mutant melanomas and evaluated the effect of corin in dose-response assays.…”
Section: Discussionmentioning
confidence: 99%
“…39 Nevertheless, for the subgroup of NRAS-mutated melanomas, P38 is shown to function as a tumor suppressor in animal models. 40 Focusing on the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), a pathway's downstream transcription regulator and controller of the balance between cell survival and death in melanoma, it has been shown that induced suppression of P38's activity enhances the NF-κB-related stimulation of Fas receptor, triggering the apoptotic cascade in early-and late-stage melanoma cells in response to UV radiation. 41 Furthermore, NF-κB seems to play a major role in the progression of metastatic melanoma by initiating anti-apoptotic instead of pro-apoptotic procedures.…”
Section: P38 Pathwaymentioning
confidence: 99%
“…Combined pharmaceutical targeting of both pathways is also more effective in mitigating tumor growth than monotherapy, 36 especially for advanced stage melanomas or for those attributed to chronic UV exposure 39 . Nevertheless, for the subgroup of NRAS‐mutated melanomas, P38 is shown to function as a tumor suppressor in animal models 40 . Focusing on the nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB), a pathway's downstream transcription regulator and controller of the balance between cell survival and death in melanoma, it has been shown that induced suppression of P38's activity enhances the NF‐κB‐related stimulation of Fas receptor, triggering the apoptotic cascade in early‐ and late‐stage melanoma cells in response to UV radiation 41 .…”
Section: Introductionmentioning
confidence: 99%